Effect of Athenium and Nitrogen in some growth parameters of local class Coriandrum sativum L. - Saad Al- (College of Education for Pure Sciences, 2005)
The study was carried out in Al-Rashccdia station-department of agricultural researeh-Ninavaduring the season 2001-2002. Anexperimentdone in field with siltv loam soil in order to investigate the e fleet of cthephon(0,240,480,720) gr./ha a,i, , and Nitrogen (0. 60, 80, 100, 120) Kg. /ha on some growth parameters of local Coriander (Coriandrumsativum L.) The results showed an increase in the values of Net Assimilation Rate (N.A.K) . Relative Growth Rale(R.G.R) , Crop Growth Rario (C.G.R) and Biological Yield by increasing the rate of Nitrogen specially at 80 kg/ha . but on the other side etticphon at all levels indicated inhibition in growth values at N.A.R. , R.G.R. , and C.G.R. except for the values of biological yields witch increased at the rate of ethephon 240 and 480 er/ha.